PEMBERDAYAAN USAHA BUDIDAYA IKAN LELE DENGAN TEKNOLOGI FITOREMEDIASI MENGGUNAKAN Ipomoea aquatica (KANGKUNG) DENGAN SISTEM CRS (Close Resirculation System) - Saad, Moch; Purnamasari, Ika (Program Studi Budidaya Perairan Universitas Mataram, 2022)
One of the management efforts to improve water quality and optimize the utilization of aquaculture wastewater is to use a closed recirculation phytoremediation system. The purpose of this activity is to apply effective and efficient technology in utilizing waste water from catfish cultivation with a closed circulation system. The method of activity is counseling and discussion, training, practice and demonstration plots as well as ongoing assistance. The PKM partner group is the â€œLestari Makmurâ€ Fish Cultivator Group in Sambangan Village, Babat District, Lamongan Regency, East Java Province. The science and technology provided is a method of utilizing waste water (Phytoremediation) from catfish cultivation using Kale (Ipomoea aquatica) with Closed Recirculation System. The spirit and motivation of the partner group is very high and enthusiastic in accepting the knowledge and applying the technology provided